Perfil da comercialização de milho de pequenos produtores no estado de Minas Gerais - Pereira Couto, Ebenezer; Martins Rezende, Alberto; Barbosa da Silva, Carlos Arthur; de Lima, João Eustáquio (Revista Ceres, 2025)
Improving marketing systems is a natural means to minimize the socio-economic problems derived from the modernization process of agriculture in developing countries. The objective of this paper was to undertake a descriptive analysis of the corn marketing system of small farmers in the State of Minas Gerais, in an attempt to provide elements for broader programs of corrective action which will exert impacts in the overall performance of the system.